Songs of experience : modern American and European variations on a universal theme - Jay, Martin, 1944- (University of California Press, 2005)
Few words in both everyday parlance and theoretical discourse have been as rhapsodically defended or as fervently resisted as "experience." Yet, to date, there have been no comprehensive studies of how the concept of experience has evolved over time and why so many thinkers in so many different traditions have been compelled to understand it. Songs of Experience is a remarkable history of Western ideas about the nature of human experience written by one of our best-known intellectual historians. With its sweeping historical reach and lucid comparative analysis - qualities that have made Martin